Embryonal Rhabdomyosarcoma of Upper Lid in 15-Year-Old Patient - Mohammad Sharifi (Case Reports in Ophthalmological Medicine)
Rhabdomyosarcoma is the most common childhood primary malignant tumor of orbit. Most of patients present between the ages of 7 and 8 years. Pure eyelid rhabdomyosarcoma is a very rare tumor with only a few reported cases in the literature. We introduce a pure embryonal rhabdomyosarcoma of upper lid in 15-year-old patient and demonstrate successful management of it.